From Green Revolution to micro-nutritient deficiency - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
India has discovered an unfortunate consequence of the Green Revolution: high yielding varieties are suffering from micro nutrient deficiencies Recent research indicates that most crops cultivated with Green Revolution material and techniques show...